Legal Protection for Women Victims of Sexual Harassment in Public Spaces in Sidoarjo Regency: Perlindungan Hukum Terhadap Perempuan Korban Pelecehan Seksual di Ruang Publik di Kabupaten Sidoarjo - Pertiwi, Tahta; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2022)
Crime in Indonesia continues to grow and lately has caused many victims in society, especially women. In general, victims of crime experienced by every woman, in addition to acts of violence, are acts of sexual harassment. Sexual harassment in Indonesia has often happened, as we know that every day many media report incidents of sexual harassment, especially harassment that occurs in public spaces. The purpose of this study is to determine the suitability of the application of the Law on the Protection of Witnesses and Victims contained in Law no. 31 of 2014 against women victims of sexual harassment in public spaces. The method used is the normative legal method. The results of the study indicate that legal protection for women victims of sexual harassment in public spaces in Sidoarjo Regency has not been fully implemented. Many victims of sexual harassment in public spaces in Sidoarjo Regency are still afraid to speak up because on average, victims of sexual harassment are still made victim blaming considering that there is very little evidence of sexual harassment in this public space.